THE IMPACT OF BRAND IDENTITY ON BRAND LOYALTY OF VIDEO GAME COMPANIES: A CASE STUDY OF BLIZZARD ENTERTAINMENT - Fauzan Wiguna, Abdalla
The video game industry is a big industry, seeing as the estimation of video game players or “gamers” in 2020 reaching 2,7 billion. While the global market of video games is valued to an estimate of $155 billion. One example of a video game company would be Blizzard Entertainment, a video game developing company created in 1991 and headquartered in Irvine, California. Video game customers, especially those playing from game consoles and from PC would be familiar of Blizzard as they have created popular games such as World of Warcraft and Diablo. Though it was created in 1991, it still creates video games and gains revenue today, regarded as one of the biggest video game companies in the world. This dissertation aims to investigate the brand identity of Blizzard and Blizzard’s methods on how to create their brand loyalty, and the impact it has towards the brand loyalty of their customers, how this dissertation will attempt to investigate on Blizzard’s brand identity methods would start from the literature review so to have an understanding of the factors such are brand identity, brand loyalty, and the variables surrounding it which then be considered to create the data collection method. The data collection method itself would be qualitative from investigating the brand identity of blizzard and Blizzard’s methods to create brand loyalty and how it correlates to Blizzard’s brand identity so to achieve brand loyalty and quantitative in the form of online questionnaires to have direct verification of blizzard customer’s brand loyalty through a Likert scale of 1 to 5 so to measure the respondents perception which 1 is scaled as “highly disagree” and 5 is scaled as “highly agree”. The questionnaire would ask on variables of Brand Identity and Brand Loyalty such as “game quality” and “customer engagement” as means to verify the brand loyalty of Blizzard customers,. The results of the research found that Blizzard creates their brand identity through their approach of core values as an organization, and their methods of creating brand loyalty comes from their approach of Brand Identity, specifically based of their core values as an organization. Moreover, results of the